Efficient Solar‐Driven Water Oxidation over Perovskite‐Type BaNbO2N Photoanodes Absorbing Visible Light up to 740 nm. Issue 24 (26th June 2018) - Seo, Jeongsuk; Hisatomi, Takashi; Nakabayashi, Mamiko; Shibata, Naoya; Minegishi, Tsutomu; Katayama, Masao; Domen, Kazunari
Abstract: Photoelectrochemical water splitting using semiconductors absorbing a wide range of visible light is a potentially attractive means of harvesting large portions of the solar spectrum. However, this is also very challenging because narrowing the semiconductor band gap lowers the driving force for photoreactions. Herein, a highly active perovskite BaNbO2 N exhibiting photoexcitation up to 740 nm for water oxidation is reported. The synthesis route, consisting of moderate nitridation and subsequent annealing in inert Ar flow, enhances the crystallinity of the BaNbO2 N surface without inducing the reduction of the Nb species. As a result, a particulate BaNbO2 N photoanode exhibits a photocurrent of 5.2 mA cm −2 at 1.23 VRHE under simulated solar irradiation, which is the highest yet reported for an oxynitride responsive at wavelengths above 600 nm. Suppressing the reduction of B‐site cations during the synthesis of perovskite AB(O, N)3, which otherwise results in surface defects or impurities, is critical for achieving high water oxidation activity. Abstract : A novel synthesis route for BaNbO2 N via mild nitridation of crystalline Ba5 Nb4 O15 and subsequent annealing under inert Ar is presented for highly efficient solar‐driven water splitting, which is never achieved from the typical, long nitridation in NH3 flow. It effectively suppresses the reduction of Nb species while enhancing the crystallinity of the oxynitride surface.